Tourist assets of Zabory in contemporary times and years past - Palmowski, Tadeusz (Turystyka i krajoznawstwo, 2021)
Interest in Pomerania developed after Poland regained independence. Mieczysław Orłowicz, a distinguished Polish ‘excursionist’ who managed the Tourist Section in the General Department in the Ministry of Public Works, brought to light and promoted in his numerous publications (mainly guidebooks) the cultural and natural environmental assets of many regions in the country including Pomerania. Based on these, the author sought to give a closer look at the part of Pomerania called Zabory. A picture of tourism in the area presented nearly a century ago is followed by that of today. The author draws attention to the natural environment of the region and environmental protection measures as well as the attractions offered by this part of the Chojnice district which favours various forms of active tourism. The article also refers to investments in tourist infrastructure including cycling, kayak and sailing facilities.